Five-Year Follow-Up of a Slowly Resorbable Biosynthetic P4HB Mesh (Phasix) in VHWG Grade 3 Incisional Hernia Repair - L. M. Van den Dop, MD; M. M. J. Van Rooijen, MD, PhD; T. Tollens, MD; L. N. Jørgensen, MD, PhD; T. S. De Vries-Reilingh, MD, PhD; G. Piessen, MD, PhD; F. Köckerling, MD, PhD; M. Miserez, MD, PhD; M. Dean, MD; F. Berrevoet, MD, PhD; B. Dousset, MD, PhD; H. L. Van Westreenen, MD, PhD; et al. (Annals of Surgery Open)
Objective:. To assess the 5-year recurrence rate of incisional hernia repair in Ventral Hernia Working Group (VHWG) 3 hernia with a slowly resorbable mesh. Summary Background Data:. Incisional hernia recurs frequently after initial repair. In potentially contaminated hernia, recurrences rise to 40%. Recently, the biosynthetic Phasix mesh has been developed that is resorbed in 12–18 months. Resorbable meshes might be a solution for incisional hernia repair to decrease short- and long-term (mesh) complications. However, long-term outcomes after resorption are scarce. Methods:. Patients with VHWG grade 3 incisional midline hernia, who participated in the Phasix trial (Clinilcaltrials.gov: NCT02720042) were included by means of physical examination and computed tomography (CT). Primary outcome was hernia recurrence; secondary outcomes comprised of long-term mesh complications, reoperations, and abdominal wall pain [visual analogue score (VAS): 0–10]. Results:. In total, 61/84 (72.6%) patients were seen. Median follow-up time was 60.0 [interquartile range (IQR): 55–64] months. CT scan was made in 39 patients (68.4%). A recurrence rate of 15.9% (95% confidence interval: 6.9–24.8) was calculated after 5 years. Four new recurrences (6.6%) were found between 2 and 5 years. Two were asymptomatic. In total, 13/84 recurrences were found. No long-term mesh complications and/or interventions occurred. VAS scores were 0 (IQR: 0–2). Conclusions:. Hernia repair with Phasix mesh in high-risk patients (VHWG 3, body mass index >28) demonstrated a recurrence rate of 15.9%, low pain scores, no mesh-related complications or reoperations for chronic pain between the 2- and 5-year follow-up. Four new recurrences occurred, 2 were asymptomatic. The poly-4-hydroxybutyrate mesh is a safe mesh for hernia repair in VHWG 3 patients, which avoids long-term mesh complications like pain and mesh infection.